Worker Participation in a Time of COVID: A Case Study of Occupational Health and Safety Regulation in Ontario - Hall, Alan; Tucker, Eric (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2022)
This study examines worker voice in the development and implementation of safety plans or protocols for covid-19 prevention among hospital workers, long-term care workers, and education workers in the Canadian province of Ontario. Although Ontario occupational health and safety law and official public health policy appear to recognize the need for active consultation with workers and labour unions, there were limited – and in some cases no – efforts by employers to meaningfully involve workers, worker representatives (reps), or union officials in assessing covid-19 risks and planning protection and prevention measures. The political and legal efforts of workers and unions to assert their right to participate and the outcomes of those efforts are also documented through archival evidence and interviews with worker reps and union officials. The article concludes with an assessment of weaknesses in the government promotion and protection of worker health and safety rights and calls for greater labour attention to the critical importance of worker health and safety representation.